Unveiling the combined effect of nano fertilizers and conventional fertilizers on crop productivity, profitability, and soil well-being - Upadhyay, Pravin Kumar; Singh, Vinod Kumar; Rajanna, G. A.; Dwivedi, Brahma Swaroop; Dey, Abir; Singh, Rajiv Kumar; Rathore, Sanjay Singh; Shekhawat, Kapila; Babu, Subhash; Singh, Tarunendu; Kumar, Yogendra; Singh, Chandu; et al. (Frontiers in Sustainable Food Systems, 2023)
It is widely accepted that deficiency of macro (nitrogen) and micronutrients (zinc, copper etc.) affects the plant growth and development which cause a significant threat to crop production and food security. The Indian Farmers Fertilizer Cooperative (IFFCO) developed nano-urea (nano-N), nano-zinc (nano-Zn), and nano-copper (nano-Cu) liquid fertilizer formulations to enhance the crop yields, simultaneously addressing the nutrient deficiency, without causing toxicity. Therefore, this study was formulated to evaluate the effectiveness of nano-N (nano-urea), nano-Zn, and nano-Cu at varying N levels [0, 50, 75, and 100% of the recommended rates of nitrogen (RRN)] on maize-wheat and pearl millet-mustard systems during 2019–20 and 2020–21. The results exhibited that the application of nano-N + nano-Zn with 100% RRN exhibited significantly higher grain yields in maize (66.2–68.8%), wheat (62.6–61.9%), pearl millet (57.1–65.4%), and mustard (47.2–69.0%), respectively, over absolute control plots and combinations of three nano-fertilizers like nano-N + nano-Zn + nano-Cu applied plots. This was mainly attributed to the higher N and Zn uptake by the crops. However, 75% RRN with nano-N + nano-Zn also produced comparable yields. Thus, applying nano-N and nano-Zn via foliar applications, in conjunction with conventional urea, has the potential to reduce the required nitrogen fertilizer amount by up to 25%, while simultaneously maintaining equivalent yield levels. Similarly, 100% RRN and 75% RRN + nano-N + nano-Zn registered comparable profitability, soil mineral N, dehydrogenase activity (DHA), and soil microbial biomass carbon (SMBC), during both the study years. However, further research and field trials on nano fertilizers alone or in combination with conventional fertilizers are essential to fully unlock its benefits and ascertain its long-term effects which may offer a pathway to more efficient and eco-friendly crop nourishment.